Simulation of the impact of higher harmonics on the transient process of induction machine fed from PWM inverters - Nenad Marković; Slobodan Bjelić; Jeroslav Živanić; Uroš Jakšić (Tehnički Vjesnik, 2017)
In this paper a fundamental mathematical model (algorithm) for determination of condition of induction machine as well as the simulation procedure for measurement of certain values in program MATLAB has been presented. A scheme of measuring system and results of simulation application are presented on output lists. Thus, measuring system gradually develops and improves as combination of information and results of previous steps in modeling with new elements essential for development of researches when induction machine is fed through PWM inverter.